From Literal to Loaded: The Semantic Pejoration in Social Media Discourse - Khalil, Uzma; Shah, Irfan Ali (Pakistan Languages and Humanities Review, 2025)
This study aims to analyze the cognitive representation of the process of Semantic change in the politically charged terms used in social media. The study uses Conceptual Blending Theory (CBT) as a framework to explore our mental processes in social interactions to create expressions which are equivalent to the metaphors and are used in a completely different meaning from its literal one. The study focused on three popular phrases for analysis: "Molana Diesel," "Mujhe Kyun Nikala," and "Program to Warr Gaya". This research shows that the phrases used in social media change the meaning of the phrases used in the political context. Social media transforms political expressions, quickly changing their meaning in everyday public conversation. The term "Diesel" might be used to indicate the fuel; however, it has changed its meaning to refer to the person of a specific political figure. Similarly, “Mujhe Kyun Nikala” has a very general meaning however, it has changed its meaning to a specific political context, reflecting both literal and political meaning. The study concludes that the cognitive underpinning of these phrases used in social media leads to the change in their meaning associated with political context. This study also concludes that the metaphoric use of terms express cultural and political ideas while also offering a new perspective on cognition and social media. This research highlights the evolving nature of language in social media which leads to semantic pejoration. Semantic pejoration can further be studied through print media discourse.